Cybersecurity Risk: Revised - Florackis, Chris; Louca, Christodoulos; Michaely, Roni; Michael Nicholas Weber (My University, 2023)
Based on textual analysis and a comparison of cybersecurity risk disclosures of firms that were hacked to others that were not, we propose a novel firm-level measure of cybersecurity risk for all U.S.-listed firms. We then examine whether cybersecurity risk is priced in the cross-section of stock returns. Portfolios of firms with high exposure to cybersecurity risk outperform other firms, on average, by up to 8.3% per year. Yet, high-exposure firms perform poorly in periods of high cybersecurity risk. Reassuringly, the measure is higher in information-technology industries, correlates with characteristics linked to firms hit by cyberattacks, and predicts future cyberattacks.
Keywords: Cybersecurity; Risk